2021
DOI: 10.21037/jgo-21-226
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of splenic volume in hepatocellular carcinoma patients receiving transarterial chemoembolization

Abstract: Background: Liver function is a key determinant for the survival of hepatocellular carcinoma (HCC) patients receiving transarterial chemoembolization (TACE). However, establishing robust prognostic indicators for liver insufficiencies and patient survival remains an unmet demand. This retrospective study evaluated the prognostic value of splenic volume (SV) in HCC patients undergoing TACE.Methods: A total of 67 HCC patients who underwent at least two consecutive TACE procedures were retrospectively included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…First, it was a single-center, retrospective study. However, the sample size was distinctly larger than that included in the previous study on this topic [ 12 ]. Additionally, our dataset was well investigated and we only included patients with complete clinical, laboratory, and imaging data.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…First, it was a single-center, retrospective study. However, the sample size was distinctly larger than that included in the previous study on this topic [ 12 ]. Additionally, our dataset was well investigated and we only included patients with complete clinical, laboratory, and imaging data.…”
Section: Discussionmentioning
confidence: 95%
“…The literature is scarce regarding the prognostic role of splenic volume for patients with HCC undergoing TACE. To date, only one recent study by Dai et al showed that splenic volume was correlated to the Child-Pugh classification and OS [ 12 ]. The mean splenic volume of the 67 patients in that study was 300 ml, prior to TACE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spleen volume, with and without adjustment to future remnant liver volume, BSA or platelets, has also been correlated with PHLF and survival [121][122][123][124][125][126][127][128][129]. The use of liver and spleen volumetry has also been studied in predicting outcomes following locoregional treatments such as thermal ablation, transarterial chemoembolisation and transarterial radioembolisation and following systemic therapy [130][131][132][133][134][135][136]. A detailed description of findings from these studies is beyond the scope of this review due to the differences and complexity of such treatments.…”
Section: Hepatocellular Carcinoma-related Outcomesmentioning
confidence: 99%